Integrasi Prinsip-Prinsip Islam dalam Kewirausahaan dan Pemasaran: Studi Literatur tentang Motivasi, Pembiayaan, dan Strategi Bisnis Berkelanjutan - Santoso, Seger; Ruslaini (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aims to explore the integration of Islamic principles in entrepreneurship and marketing, focusing on motivation, financing, and sustainable business strategies. Using a qualitative literature review approach, the study identifies Islamic values such as amanah (trust), sidq (truthfulness), and justice as the foundation of Muslim entrepreneurs' motivation. In the financing aspect, Sharia-compliant instruments like mudharabah and musharakah are found to provide equitable financial solutions, despite challenges in financial literacy. Islamic marketing strategies, including Islamic branding and halal marketing, significantly contribute to building consumer loyalty and business sustainability. The study highlights the importance of collaboration among entrepreneurs, financial institutions, and policymakers to create an inclusive Islamic business ecosystem. The findings offer conceptual guidance for developing ethical and sustainable Islamic entrepreneurship